Faktor-faktor yang mempengaruhi pendapatan wanita di sektor informal (studi kasus pedagang Kecamatan Pasar Muara Bungo) - Ainun Iliana, Desra; Junaidi, Junaidi; Hardiani, Hardiani (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study aims to determine how the influence of the number of dependents, location, capital, education and marital status on the income of women in the informal sector in the sub-district Pasar Muara Bungo Bungo Regency. the population in this study were women traders in sub-district Pasar Muara Bungo. The data collection method used was a questionnaire. By using the Ordinary Least Square (OLS) method. Based on the results of regression analysis that simultaneously the number of dependents, location, capital, education and marital status have a significant effect on women traders in the informal sector, while partially the variables of the number of dependents, capital, education and marital status have a positive and significant effect on the income of women traders in the informal sector while location has no significant effect on the income of women traders in the informal sector in sub-district Pasar Muara Bungo, Bungo Regency.